Aqueous phase selective detection of 2, 4, 6-trinitrophenol using a fluorescent metal–organic framework with a pendant recognition site1. Issue 34 (14th September 2015) - Nagarkar, Sanjog S.; Desai, Aamod V.; Samanta, Partha; Ghosh, Sujit K.
<x xml:space="preserve">Abstract</x> A metal–organic framework with a pendant Lewis basic recognition site was employed to achieve selective detection of the nitro explosive TNP in the aqueous phase.